Effects of 12-week medicine ball training on muscle strength and power in young female handball players - Ignjatovic, A. M.; Markovic, Z. M.; Radovanovic, D. S. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine the effects of medicine ball training on the strength and power in young female handball athletes. Twenty-one young female handball players (age, 16.9 ± 1.2 years) were randomly assigned to experimental and control groups. Experimental group (n = 11) participated in a 12-week medicine ball training program incorporated into the regular training session, whereas controls (n = 10) participated only in the regular training. Performance in the medicine ball throws in standing and sitting positions, 1 repetition maximum (1RM) bench and shoulder press, and power test at 2 different loads (30 and 50% of 1RM) on bench and shoulder press were assessed at pre- and posttraining testing. The athletes participating in the medicine ball training program made significantly greater gains in all medicine ball throw tests compared with the controls (p < 0.01). Also, the experimental group made significantly greater gains in bench and shoulder press power than control group (p < 0.05). Both training groups (E) and (C) significantly (p < 0.05) increased 1RM bench and shoulder strength, with no differences observed between the groups. Additionally, medicine ball throw tests showed stronger correlation with power tests, than with 1RM tests. These data suggest that 12-week medicine ball training, when incorporated into a regular training session, can provide greater sport-specific training improvements in the upper body for young female handball players.